To convert the equation from vertex form \( y = -4(x + 5)^2 - 3 \) to standard form, we will expand the squared term and simplify the expression.
-
Start with the vertex form: \[ y = -4(x + 5)^2 - 3 \]
-
Expand the squared term: \[ (x + 5)^2 = x^2 + 10x + 25 \]
-
Substitute this back into the equation: \[ y = -4(x^2 + 10x + 25) - 3 \]
-
Distribute \(-4\): \[ y = -4x^2 - 40x - 100 - 3 \]
-
Combine like terms: \[ y = -4x^2 - 40x - 103 \]
So, the standard form of the equation is: \[ y = -4x^2 - 40x - 103 \]
The correct response is: y = −4x² − 40x − 103.